Gestational diabetes in rural central India: low prevalence but absence of typical risk factors. Issue 7 (July 2021) - Chebrolu, Puja; Kurbude, Ravi; Thakur, Manju; Shah, Naman; Jain, Rachna
Abstract: Introduction: The reported prevalence of gestational diabetes mellitus (GDM) varies widely across India. Given the short-term, long-term, and multigenerational health impacts of GDM, understanding its frequency and risk factors is important for population screening strategies. We estimated the prevalence of GDM and determined associated risk factors in rural, central India, where data is sparse. Methods: We conducted a cross-sectional study of a convenience sample of 575 pregnant women attending antenatal care (ANC) clinics at Jan Swasthya Sahyog's (JSS) outreach clinics in rural Chhattisgarh, India. Study participants underwent a non-fasting 75g oral glucose tolerance test (OGTT) between 24-28 weeks gestation. Using Diabetes in Pregnancy Study Group of India (DIPSI) criteria, a 2-hour post-OGTT glucose ≥140 mg/dL was used to diagnose GDM. Results: We found 11 patients (1.9%) who met diagnostic criteria for GDM. Median age, systolic blood pressure, and diastolic blood pressure were higher in those with GDM (26 vs 23 years, p = 0.02; 117 vs 106 mmHg, p = 0.04, 77 vs 68 mmHg, p < 0.01, respectively). Pre-hypertension was associated with increased odds of GDM on multivariate analysis (OR 4.0, 95% CI: 1.1, 14.8). BMI was not associated with GDM. With appropriate management there were no differences in fetal complications between GDM and normal glucose tolerance (NGT) groups. Conclusions: In rural, central India the prevalence of GDM was 1.9% in the absence of traditional risk factors such as increased BMI. Further research is needed to define the applicability of optimal screening strategies in such settings. Abstract : Gestational diabetes; India; Screening.